Digital literacy development of undergraduate students for Society 5.0: pedagogical implication for language and science education - Madayani, Nany Soengkono; Iftanti, Erna; Ningrum, Ary Setya Budhi (JEELS (Journal of English Education and Linguistics Studies), 2025)
The rapid advancement of technology in the era of Society 5.0 has reshaped education, leading this study to investigate how students develop and strengthen their digital literacy skills. This qualitative research was conducted among students from the Language and Science Departments of a state Islamic university in Tulungagung, Indonesia. From 174 students responding to the questionnaire, twelve were purposively selected for in-depth interviews based on their high level of digital literacy. Data were analyzed thematically using a systemic qualitative approach that involved cross-verifying interview findings with observational data. Findings reveal that internal factors such as curiosity about technology, intrinsic motivation, learning needs, and preference for digital tools strongly influence students’ digital literacy. External factors—particularly social environment, academic culture, and lifestyle— were found to enhance these skills. Pedagogically, this study proposes transformative strategies such as the integration of online laboratories (OLABS), digital-based learning systems, and technology-oriented competitions. As a transformative study, it calls for Islamic higher education institutions to foster a digitally enriched learning ecosystem that aligns with the demands of Society 5.0.